Jerzy Wehr - Archives of Acoustics, Editorial Committee of (Archives of Acoustics, 1978)
Jerzy Wehr, 54, professor, for many years the scientific worker of the Institute of Fundamental Technological Research, Polish Academy of Sciences, lost his life in the prime of his creative forces, as a member of a climbing expedition in Hindu Kush at the altitude of 6000 m on August 10th, 1977.